The Effects of Total Quality Management Practices and Marketing on Performance of SMEs. A Case of Selected Manufacturing Industries, Greece - Kalogiannidis, Stavros Ioannis (Business Management and Strategy, 2021)
Most global studies have to a greater extent underscored the importance of Total quality management practices and some marketing aspects concerning organizational performance. Most studies have focused on establishing the level to which TQM practices influence customer satisfaction and not the whole organization. There is also little evidence on how marketing practices influence organizational performance. This study therefore seeks to assess the impact of Total Quality management practices and marketing on organizational performance. Data was collected from a sample size of 289 respondents who were employees of the different manufacturing industries in Greece. Data was analyzed using SPSS and Pearson’s rank correlation coefficient was used to establish the relationship between study variables. The study findings confirmed the presence of a relationship between TQM practices and organizational performance. Similarly there was a positive relationship between marketing practices and organizational performance. The study concluded that the TQM practices and marketing are great influencers of quality hence should always be applied in organizations.